KECAKAPAN BERPIKIR KREATIF DALAM PEMBELAJARAN IPA DI KELAS V MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) - Fuji Nurmaelani; Jajang Bayu Kelana; Ruli Setiyadi (IKIP Siliwangi, 2021)
This research was motivated by the low ability of creative thinking in elementary schools. The method used in this research was descriptive qualitative research method. The research population was the fifth-grade students of SDN 2 Lembang, Lembang, West Bandung Regency. while the selected sample was 37 students with convenience technique. The result of this research was increasing students' creative thinking ability. The research concluded that the Number Heads Together learning model affected an increase in creative thinking ability, especially in science study.